Scenario-based functional modularization framework for consumer electronics using MFD and AHP: A case study on audio products - Zhengda Wu; Jie Zhang (PLoS ONE, 2025)
Consumer Electronics (CE) currently face dual pressures: the growing demand for personalization and multi-scenario usage, and the need to enhance product sustainability. Traditional single-function designs struggle to adapt to these changes, leading to resource underutilization and the generation of significant electronic waste (e-waste). Consequently, there is an urgent need for a design method capable of systematically partitioning product functions based on distinct scenarios. However, existing modularization approaches predominantly focus on production efficiency, often failing to address multi-scenario user needs or effectively reduce e-waste. To address this gap, this paper proposes a scenario-based functional modularization framework. This framework integrates Modular Function Deployment (MFD) with the Analytic Hierarchy Process (AHP) to quantify scenario-specific requirements and establishes a Modular Scenario Relevance Matrix (MSRM) to achieve precise mapping between technical solutions and specific scenarios. A case study on audio products verified the feasibility of the framework, successfully identifying a common module and several scenario-specific functional modules (e.g., home entertainment, smart home, outdoor). This study provides designers with a systematic method for developing flexible and adaptable CE products, demonstrating how scenario-driven modularity can enhance product sustainability by reducing functional redundancy and e-waste while satisfying diverse consumer demands.